Проблема людини у філософії Г. Сковороди - Борн, С. О. (ХНУРЕ, 2019)
The thesis is devoted to one of the most important aspects of the philosophy of Gregory Skovoroda - the question of the meaning and content of human life. First of all, Skovoroda offers a philosophical and religious approach to the solution of this issue. In this case, he relies on the idea of the duality of the world, which finds its manifestation and in being human. The philosopher pays special attention to human qualities like love and faith. They, in his opinion, should be the basis of human existence.